2020
DOI: 10.48550/arxiv.2011.01714
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

DNN-based mask estimation for distributed speech enhancement in spatially unconstrained microphone arrays

Abstract: Deep neural network (DNN)-based speech enhancement algorithms in microphone arrays have now proven to be efficient solutions to speech understanding and speech recognition in noisy environments. However, in the context of adhoc microphone arrays, many challenges remain and raise the need for distributed processing. In this paper, we propose to extend a previously introduced distributed DNN-based timefrequency mask estimation scheme that can efficiently use spatial information in form of so-called compressed si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…This achieved better performance than with an oracle VAD. In an extended study, we generalized these results to real-life scenarios and showed that sending the noise estimate rather than the target estimate could improve the performance depending on the source to interferences ratio (SIR) at the receiving node [17]. To take full advantage from the spatial coverage of the distributed microphone array, in the following, both the target and noise 1 estimates will be sent as represented in Figure 1.…”
Section: Dnn-based Distributed Multichannel Wiener Filtermentioning
confidence: 99%
See 4 more Smart Citations
“…This achieved better performance than with an oracle VAD. In an extended study, we generalized these results to real-life scenarios and showed that sending the noise estimate rather than the target estimate could improve the performance depending on the source to interferences ratio (SIR) at the receiving node [17]. To take full advantage from the spatial coverage of the distributed microphone array, in the following, both the target and noise 1 estimates will be sent as represented in Figure 1.…”
Section: Dnn-based Distributed Multichannel Wiener Filtermentioning
confidence: 99%
“…It is denoted "SN". The second model is the model that has been used in our previous experiments [17]. It is a multi-node neural network that estimates the mask based on the local reference signal and the compressed signals sent from the other nodes.…”
Section: A Modelsmentioning
confidence: 99%
See 3 more Smart Citations